Karakteristik Perusahaan dan Struktur Kepemilikan Sebagai Determinan Struktur Modal, Kinerja Keuangan, serta Nilai Perusahaan - Purbawangsa, Ida Bagus; Suana, I Wayan (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 13 Nomor 2 Tahun 2019, 2019)
The purpose of this study was to determine the determinants of company characteristics and ownership structure as drivers, improvement of capital structure, financial performance, and firm value in consumption companies on the Stock Exchange. Population data in this study are all consumption companies that have gone public in the period of 2009 to 2016. The selection and determination of the sample in this study was conducted based on purposive sampling technique, namely the technique of sampling which was intentionally based on the criteria set by the researcher. Precise Judgment Sampling, where the sample chosen uses certain criteria that must be in accordance with the research objectives. Consumption companies are very  important companies. Companies that are able to  help  move the economy, help the government, create many jobs, but there are still many raw materials depending on imported materials. The government is expected to be able to make policies that  can  maintain  Macroeconomics, especially  the  stability  of  the  rupiah.  Improving infrastructure that can have an efficient impact on the distribution of goods and opening new consumer opportunities. Keywords: company characteristics, company value, investor